VHL Genetic Alteration in CCRCC Does Not Determine De-Regulation of HIF, CAIX, hnRNP A2/B1 and Osteopontin. (2010) - Nyhan, Michelle J.; El Mashad, Shereen M.; O'Donovan, Tracey R.; Ahmad, Sarfraz; Collins, Chris; Sweeney, Paul; Rogers, Eamonn; O'Sullivan, Gerald C.; McKenna, Sharon L.
Abstract : Background : von Hippel–Lindau ( VHL ) tumour suppressor gene inactivation is associated with clear cell renal cell carcinoma (CCRCC) development. The VHL protein (pVHL) has been proposed to regulate the expression of several proteins including Hypoxia Inducible Factor-α (HIF-α), carbonic anhydrase (CA)IX, heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 and osteopontin. pVHL has been characterized in vitro, however, clinical studies are limited. We evaluated the impact of VHL genetic alterations on the expression of several pVHL protein targets in paired normal and tumor tissue. Methods : The VHL gene was sequenced in 23 CCRCC patients and VHL transcript levels were evaluated by real-time RT-PCR. Expression of pVHL's protein targets were determined by Western blotting in 17 paired patient samples. Results : VHL genetic alterations were identified in 43.5% (10/23) of CCRCCs. HIF-1α, HIF-2α and CAIX were up-regulated in 88.2% (15/17), 100% (17/17) and 88.2% (15/17) of tumors respectively and their expression is independent of VHL status. hnRNP A2/B1 and osteopontin expression was variable in CCRCCs and had no association with VHL genetic status. Conclusion : As expression of these proposed pVHL targets can be achieved independently of VHL mutation (and possibly by hypoxia alone), these data suggests that other pVHL targets may be more crucial in renal carcinogenesis.